Kingdoms in Peril : A Novel of the Ancient Chinese World at War. - Milburn, Olivia (University of California Press, 2022)
This abridged edition introduces readers to the power and drama of this electrifying classic Chinese novel. One of the great works of Chinese literature, beloved in East Asia but virtually unknown in the West, Kingdoms in Peril is an epic historical novel charting the five hundred years leading to the unification of China under the rule of the legendary First Emperor. Writing some fourteen hundred years later, the Ming-era author Feng Menglong drew on a vast trove of literary and historical documents to compose a gripping narrative account of how China came to be China. Here, translated into.